Forensic odontology : an essential guide - Adams, Catherine, 1960-; Carabott, Romina; Evans, Sam, 1976- (Chichester, West Sussex : John Wiley & Sons Inc., 2013)
An accessible, essential introduction to forensic odontology. Written by a team of well-established, active practitioners in the field, Forensic Odontology is invaluable for those needing an introduction to the subject for the general dental practitioner who has an interest in forensic dentistry and is contemplating practicing in the field. It will also be useful as a reference during practice. After a brief introduction the book covers dental anatomy and development, expert witness skills, mortuary practice, dental human identification, disaster victim.
Introduction-editors -- Dental anatomy & development / Alastair Sloan -- Expert witness skills / Jason Tucker -- Mortuary practice / Ali Anderson -- Dental human identification / Romina Carabott -- Disaster victim identification / Cath Adams -- Dental age assessment / Sakher J. Al Qahtani -- Bite marks 1 / Douglas Sheasby -- Bite marks 2 / Roland Kouble -- Forensic photography / Sam Evans -- The role of the fo in protection of the vulnerable person / Catherine Adams & Barbara Chadwick.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Dental jurisprudence; Medicine; Odontology; Electronic books; Electronic books